PV fed Water Pumping System in a Smart Home - S., Krithiga; Sarathi Subudhi, Partha (International Journal of Engineering and Technology, 2018)
This paper proposes renewable energy based water pumping system in a smart home using a bidirectional DC-DC converter. A backup battery is connected in the system for uninterrupted power supply to the water pump. Depending upon source availability, DC-DC Â Â Â Â Â Â converter acts either in boost mode or in buck mode to supply uninterrupted power to the water pump. Using MATLAB/Simulink Â Â Â Â Â software, the proposed system is simulated and its performance is analyzed for various operating conditions and the results are furnished in this paper. A small scale laboratory prototype is fabricated and tested for the designed system. Experimental results acquired from the prototype testing correlates with the simulation results validating the feasibility of the proposed water pumping system.Â